The Influence of Competency Development and Work Motivation on The Performance of KSP Coblong Pamor Employees - Sudana, I Ketut; Kresna Wirawan, I Dewa Gede; Siti Firmani, Putu (International Journal of Management Science and Information Technology, 2024)
The research with the title "The Influence of Competency Development and Work Motivation on the Performance of "KSP Coblong Pamor" Employees aims to find out: (1) To find out the significant influence of Competency Development on the Performance of "KSP Coblong Pamor" Employees, (2) To find out the significant influence of Motivation Work on the Performance of "KSP Coblong Pamor" Employees, and (3) To determine the significant influence of Competency Development and Work Motivation together on the Performance of "KSP Coblong Pamor" Employees. The data analysis technique used is linear regression of two predictors. To find out whether the influence of the independent variable on the dependent variable is real, testing is carried out by carrying out regression analysis, namely analysis of the variance of the regression line to find the F value of the regression line, which can then be tested whether the F value is significant or not, then look for the Relative Contribution (SR) of each - each predictor X1 and The research subjects were 12 KSP Coblong Pamor employees, and the research object was competency development, work motivation and employee performance. Based on the results of the prediction analysis of two predictors, namely, X1 (competence development) and X2 (work motivation) on criterion Y (employee performance), the price F is obtainedreg of 8.45.  With (N-m-1) in this case db = 9/2 with a significance level of 5% F valuetable of 5.14. This means that the regression line analyzed is significant to be used as a basis for predictions because there is a significant contribution between the criteria (Y) and the predictors (X1, X2).  The Relative Contribution (SR) in % of each predictor is: Predictor X1 = 61.15%, and Predictor Based on these results, the regression line is 38.49%, which consists of the effective contribution of predictor X1 (competency development) = 23.54%. And the effective contribution of predictor X2 (work motivation) = 14.95. Meanwhile, the remaining 61.51% is influenced by other factors. Based on the results of the analysis above, it is hoped that employees can improve their competence by participating in training and that the leadership can also provide positive motivation to employees, so that employee performance can increase.